2019 IEEE Global Communications Conference (GLOBECOM) 2019
DOI: 10.1109/globecom38437.2019.9013444
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Cell MIMO Transceiver Design for Mission-Critical Communication

Abstract: Business and Mission critical communication (MCC) is a major communication paradigm that is used by public agencies, e.g., during emergency situations, or critical infrastructure companies, e.g., airports, transportation, etc. MCC has very stringent requirements in terms of reliability, coverage and should offer group communications. Coordinated Multimedia Multicast/Broadcast single frequency network (MBSFN) is considered as a potential technology for MCC as it benefits from increased coverage and inter-cell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, it can replaced with any other linear receiver models such as zero-forcing, matched filter, etc. In our previous work [49], we performed the comparative analysis of utilization of different filters for legitimate users and concluded that MMSE-based receiver was performing the best. With the intention to provide same benefits to the eavesdroppers and for the ease of readiness we assume the eavesdropper filters to be implemented as MMSE filter.…”
Section: B Transceiver Modelmentioning
confidence: 99%
“…However, it can replaced with any other linear receiver models such as zero-forcing, matched filter, etc. In our previous work [49], we performed the comparative analysis of utilization of different filters for legitimate users and concluded that MMSE-based receiver was performing the best. With the intention to provide same benefits to the eavesdroppers and for the ease of readiness we assume the eavesdropper filters to be implemented as MMSE filter.…”
Section: B Transceiver Modelmentioning
confidence: 99%
“…A preliminary version of this paper has been published in [41]. This reference neither include the security issue nor the norm-bounded error model.…”
Section: A Related Workmentioning
confidence: 99%